Influence of VBA-based Monopoly Game in Microsoft Excel as Teaching Material on Primary School Students' Cross-Cultural Competence in Social Studies Learning - Rahayu, Galih Dani Septiyan; Arga, Hana Sakura Putu (Mimbar Sekolah Dasar, 2019)
The background of this research is based on diversity of Indonesia in terms of social, cultural, religious, language and ethnic groups. The specific problem in this research lies on the diversity of students in one public elementary school in Cimahi City, situated in the area of the Indonesian Army. Therefore, this research seeks to investigate the difference in improvement of students cross cultural skills between learning using VBA (Visual Basic of Application)-based Monopoly game teaching materials in Microsoft Excel and conventional learning. This research aims at improving students cross cultural skills, and observing the differences or disconnection of the improvement of students cultural skills between learning using VBA-based teaching materials and conventional learning. This research employed a quasi-experimental method with a non-randomized pretest-posttest control group design. A quantitative observation instrument in the form of a checklist was used as the research instrument. The results revealed that both learning using a teaching material of VBA-based Monopoly in Microsoft Excel and conventional learning were able to improve the students cross cultural skills. However, based on the result of N-Gain test, learning using teaching material of VBA-based Monopoly game in Microsoft Excel was better than conventional learning.